Hubungan aktivitas fisik dan kebiasaan jajan dengan prevalensi gizi lebih pada anak usia sekolah di Kota Bekasi - Gultom, Ezri Yohanna; Sartika, Arindah Nur (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Overnutrition in school-aged children (6–12 years) in Indonesia continues to increase and has become a serious health issue. This condition is characterized by fat accumulation due to energy imbalance, with a BMI/A of >+1 SD to +2 SD at risk of over-nutrition. The increasing prevalence in Bekasi City emphasizes the urgency of interventions to prevent long-term impacts on children's health.Objectives: This study aimed to explain the relationship between physical activity, snack consumption patterns, and the risk of overnutrition in school children in Bekasi. Methods: This quantitative, cross-sectional study involved 215 children in grades V–VI of elementary school selected through consecutive sampling. Physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C) categories: light physical activity (≥ 1 to < 2), moderate (≥ 2 to< 5), heavy (value 5), and frequency of snack consumption using the Food Frequency Questionnaire (FFQ), and nutritional status using body mass index/A index. The study locations included five public elementary schools in Bekasi City: SDN Aren Jaya XVIII, SDN Bekasi Jaya IV, SDN Margahayu XII, SDN Duren Jaya XIV, and SDN Duren Jaya V.Results:The chi-square test showed no significant relationship between physical activity and overnutrition (OR = 1.44; 95% CI: 0.63–3.33; p = 0.389) or between snacking habits and overnutrition (OR = 0.73; 95% CI: 0.41–1.32; p = 0.301).  Conclusion: Overnutrition among schoolchildren remains a problem, with pocket money being a significant factor, whereas physical activity and snacking habits are unrelated to obesity. Pocket money management and promotion of healthy eating patterns in schools should be considered in comprehensive intervention policies.